Awlawiyāt al-Da‘wah fī al-Mujtama‘ al-Mālizī - Hashim, Jamil (Jurnal Usuluddin, 2003)
The study attempts to analyse the issue of priority in da’wah works in Malaysia. The concept of priority from the Islamic point of view will be highlighted. In addition, the writer has identified some issues of da’wah which need to be given attention to performing da’wah work in Malaysia. This include the significance of unity among the da’wah movements, the da’wah to non-muslim, the role of da’wah in facing new challenges and the importance of knowledge, expertise, skill, accumulation of information and resource centers for the use of the ummah especially the du’at.